The Fusion Impact of Compost, Biochar, and Polymer on Sandy Soil Properties and Bean Productivity - Kheir, Ahmed M.S.; Govind, Ajit; Zoghdan, Medhat G.; Khalifa, Tamer; Aboelsoud, Hesham; Shabana, Mahmoud Mohamed Abd ElHay (MDPI, 2024)
Two of the most significant issues confronting arid and semi-arid countries are soil degradation and the need to reclaim sandy soils and improve their properties to enhance the agricultural area and ensure food security. Many attempts to improve sandy soil properties have been attempted using soil amendments, but further research is needed to explore the combined impact of cost-effective amendments. To that purpose, we investigated the impact of various soil amendments, including single and combination applications of synthetic Super Absorbent Polymer (SAP), compost, and biochar, on sandy soil physiochemical characteristics and bean (Vicia faba L.) production and quality throughout three growing seasons. In a randomized complete block design with three replicates per treatment, different treatments such as control (without application), lower dose of SAP (SAP1), higher dose of SAP (SAP2), biochar, compost, SAP1 plus biochar, SAP1 plus compost, SAP2 plus biochar, SAP2 plus compost, and biochar plus compost were used. The combined treatments, such as SAP2 plus biochar (T8), SAP2 plus compost (T9), and biochar plus compost (T10), improved soil physiochemical characteristics and crop production significantly. Application of T10 decreased soil bulk density by 15%, 17%, and 13% while increasing soil available water by 10%, 6%, and 3% over the first, second, and third growing seasons, respectively, compared to untreated soil (T1). The application of treatment (T9) surpassed other treatments in terms of yield, quality, and economic return, significantly increasing the seed yield by 24%, 26%, and 27% for the first, second, and third season compared with untreated soil. The higher rate of polymer combined with compost could be considered a cost-effective soil amendment to improve sandy soil productivity in arid and semi-arid regions.